1988
DOI: 10.1128/aem.54.10.2432-2438.1988
|View full text |Cite
|
Sign up to set email alerts
|

Survival of rifampin-resistant mutants of Pseudomonas fluorescens and Pseudomonas putida in soil systems

Abstract: The fate of spontaneous chromosomal rifampin-resistant (Rifr) mutants of Pseudomonas putida and Pseudomonasfluorescens in sterile and live organic soil from which they were isolated was studied. In sterile native-soil assays, a Rifr mutant of P. putida showed no decrease in competitive fitness when compared with the wild-type parent. However, mutants of P. fluorescens were of two general categories. Group 1 showed no difference from the wild type in terms of growth rate, competitive fitness, and membrane prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(95 citation statements)
references
References 27 publications
6
89
0
Order By: Relevance
“…The population dynamics of both the separate and mixed introduced strains in soil and wheat rhizosphere, i.e. a gradual decline of cfu counts over time, with enhanced numbers of introduced organisms occurring in the rhizosphere (for the mixed introductions), was similar to that often described in other reports of introduced fluorescent pseudomonads [3,[13][14][15][16][17]. Abiotic (e.g.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The population dynamics of both the separate and mixed introduced strains in soil and wheat rhizosphere, i.e. a gradual decline of cfu counts over time, with enhanced numbers of introduced organisms occurring in the rhizosphere (for the mixed introductions), was similar to that often described in other reports of introduced fluorescent pseudomonads [3,[13][14][15][16][17]. Abiotic (e.g.…”
Section: Discussionsupporting
confidence: 78%
“…This might indicate the second colonizers encountered different colonization sites in soil than the primary colonizers, even though the final soil moisture was kept similar. It is not clear why this was observed in the light of previouslydescribed niche exclusion for P. fluorescens and P. putida strains sequentially added to soil [14].…”
Section: Discussionmentioning
confidence: 83%
“…The ecological disadvantage for a strain which results in its inability to dislodge a primary colonizer, has already been described by Compeau et al [34] in a soil study with a strain of P. fluorescens and a rifampicin-resistant mutant. They showed that the order of inoculation was determinant: the first introduced organism inhibited the development of the challenging one.…”
Section: Discussionmentioning
confidence: 60%
“…Altern.~tive!y, the higher final density of the wild-type isolate may have prevented the increase in number of the challenging engineered strain. Pseudomonas fluorescens derivatives harboring either chromosomal Tn5 insertions or rifampin mutations also exhibited a decreased ability, to colonize sterile soil when competing with their isogonic counterpart [39,40]. 32 days after the mixed inoculation in sterile microcosms, the addition Of a protozoa-free microflora led to a decline of both E. coil populations densities ( Fig.…”
Section: Resultsmentioning
confidence: 97%